ANALISIS KOMPARASI SUMBER AIR YANG BERBEDA DALAM PENGELOLAAN TAMBAK TERHADAP HASIL PRODUKSI UDANG VANNAMEI (Litopenaeus vannamei) - Sukimin Sukimin; Muhamad Agus; M Bahrus Syakirin (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2017)
Water quality is one of the major factors in the success aquacultur vannamei shrimp in ponds. This study aims to determine differences in the different water sources in the management of ponds for the production of vannamei shrimp (Litopenaeuse vannamei). The method used in this study exploratory kompar with descriptive analysis of qualitative and quantitative. Statistical t-test results on the water quality of the pond water boreholes and water sources tidal pond in the mornings and evenings differ significantly consisting of salinity, temperature, dissolved oxygen, pH, brightness and ammonia. Production results obtained pond water source wells drilled better gained an average of 2850 kg, FCR 1.2, SR 93.7% growth and weight of 26.3 grams / tail, then the tidal pond water source gained an average of 2052, 5 kg, FCR 1.6 SR 92.7% growth and weight of 20 grams /. Suggestions vannamei shrimp culture with artesian well water sources need to be tail. Conclusions water quality and production wells drilled pond water better than water tidal pond applied and developed society to farmers and water quality observation needs to be done carefullyKeywords : Vannamei shrimp aquaculture, water quality, the result of production.